ON MULTIDIMENSIONAL FIXED POINT THEOREMS IN ORDERED V-FUZZY b-METRIC SPACES - Happy Hooda, Manjeet Rathee,Archana Malik (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this article, we establish some coincidence point and common fixed pointtheorems in the recently introduced notion of partially ordered V-fuzzy b-metric spaces for  -construction. Using the results, suitable conditions are framed to make sure the existence of multidimensional coincidence point and common fixed point results, which generalize and improve fixed point results of Gupta and Kanwar [13].